Value of fish oil in nutrition therapy in Covid-19 illness - Jonathan Asprer (Indonesian Nutrition Association, 2022)
Our expertise in the medical treatment of COVID-19 infections has grown with time and experience, resulting in the development of a cohesive overall therapeutic strategy for control of the viral infection from supportive measures for mild to moderate illness, to the full range of relevant organ support in critical illness in ICU. In parallel, our strategies for providing nutrition therapy have also evolved beyond the mere delivery of macronutrients (calories and protein) to the utilization of specific nutritional substrates that may play an important role in modifying the course of the disease and optimizing clinical outcomes.